"Crisis Gets Served Before Anything Else": Structural constraints on integrating lgbt consciousness‐raising into antiviolence work. Issue 1 (May 2017) - RIOS, AISHA
Abstract : This article explores structural constraints on knowledge production and practice among volunteer members of a community‐based coalition in a southern U.S. state that addresses intimate partner violence among those whom identify as lesbian, gay, bisexual, and transgender (LGBT). Male violence against women is a serious social problem and sufficient support systems are lacking. The availability of competent support systems for LGBT‐identified persons affected by intimate partner violence is even grimmer. In response to this epidemic, advocacy organizations have responded through policy, advocacy, service provision, education, and training. This article focuses on one community‐based coalition to explore the ways hegemonic discourses interplay with organizational structure, fear, and a crisis mode orientation to shape the ways people advocate for social change and justice causes. This ethnographic research reveals the ways sociopolitical structures constrain members' willingness to explore alternatives outside of the hegemonic frameworks guiding understandings of and responses to intimate partner violence.